Pengaruh Kualitas Pelayanan Terhadap Minat Menabung Nasabah Pada Bank BSI (Bank Syariah Indonesia) Cabang Serang Banten - Nur Falih Anwar; Indah Cahyani Kartika; Della Wati; Henny Saraswati; Wahyu Hidayat; Budi Sudrajat (Journal of Islamic Banking, 2023)
This study was carried out to evaluate the level of customer satisfaction and saving intentions at Bank Syariah Indonesia (BSI). This study employed a quantitative survey method as its methodology. Up to 30 students from UIN SMH BANTEN's Faculty of Islamic Economics and Business have respondents to the survey. Statistical techniques for descriptive and inferential analysis were used to examine the acquired data. The aim of this study is to comprehend how customer interest in saving at Bank Syariah Indonesia (BSI) is influenced by service quality. The study's findings demonstrate that customer interest in saving with Bank Syariah Indonesia (BSI) is positively and significantly impacted by service quality. The association between the client's interest in saving money and the quality of the services provided is moderate, which implies that it is neither too strong nor too weak but nonetheless substantial. Customers' interest in saving at Bank Syariah Indonesia (BSI) is affected by other variables in 71.5% of the variable, with the remaining 28.5% coming from the service quality variable.